TEACHING WRITING AT THE PRIMARY LEVELS - Swandi, Irda Sulastri Binte; Netto-Shek, Jo-Ann (Universitas Pendidikan Indonesia, 2017)
Writing is a critical skill for young learners to master for academic purposes and as a work and life skill. This paper is part of a larger study on the English Language 2010 syllabus and its national curriculum in Singapore particularly in the area of the teaching of writing at the primary levels. In this paper, we report findings from a quantitative content analysis of both the syllabus and the curriculum as â€œpolicy textsâ€ (Ball, 2005) to locate alignments and variances in a discussion of their potential impact on classroom instruction. Findings from the analysis of these documents reveal that, on the whole, the national curriculum is aligned not only to current approaches for the teaching of writing but also to the syllabus in terms of instructional principles. However, the findings also reveal a difference in terms of emphasis between both documents that may potentially restrict the realisation of syllabus outcomes in the area of writing instruction at the primary levels.